ZnO-(Cu/Ag)TCNQ heterostructure network over flexible platform for enhanced cold cathode application. (18th May 2016) - Pal, Shreyasi; Maiti, Soumen; Maiti, Uday Narayan; Chattopadhyay, Kalyan Kumar
Abstract: Multistage field emitters consisting of organic/inorganic hybrid nanostructures with branched geometry are designed via a two-step protocol: a simple wet chemical method followed by a vapor-solid-phase technique. (Cu/Ag)TCNQ (copper/silver-7, 7, 8, 8-tetracyanoquinodimethane) nanowires (NWs) were grown hierarchically on zinc oxide (ZnO) nanorods (NRs) to form ZnO-(Cu/Ag)TCNQ heterostructure assemblies. By monitoring the metallic Cu and Ag coating thickness on ZnO NRs, precise control over the morphology and orientations of the secondary organic NWs is achieved. In-depth analysis of electron field emission (FE) behavior of the ZnO-(Cu/Ag)TCNQ-based hierarchy suggests highest emission performance with low turn-on as well as threshold fields of 1.15 and 3.75 V μ m −1 respectively from the morphology-optimized hierarchy. Beneficial orientation of the branched organic NWs ensures sequential electric field enhancement in the consecutive stem and branches whereas its low work function eases electron emission; these aspects combined together render an overall enhancement in the emission behavior of the hybrid system. As compared to individual building units, the heterostructures show improved field electron emission. Additionally, successful construction of this novel hybrid over a fabric platform displays great potential in opening up new pathways in the highly-anticipated field of flexible electronics.